Ag-Catalyzed minisci C–H difluoromethylarylation of N-heteroarenes. Issue 3 (7th January 2020) - Xie, Xiaojuan; Zhang, Yifang; Hao, Jian; Wan, Wen
Abstract : A mild silver-catalyzed decarboxylative C–H difluoromethylarylation of electron-deficient N-heteroarenes. Abstract : A mild silver-catalyzed decarboxylative difluoromethylarylation of electron-deficient N-heteroarenes has been developed by using aryldifluoro acetic acid as difluoromethyl sources. This protocol provides an efficient and straightforward access to difluoromethylated heteroarenes in moderate to excellent yields with good selectivities. Furthermore, this reaction was applicable to bioactive heteroarenes, providing a straightforward approach for the late-stage C–H difluoromethylation of pharmacophores.